The Influence of Dynamic Capabilities and Transformational Leadership on the Performance of Public Sector Organizations - Tri Haryanto; Alfira Sofia (Ilomata International Journal of Social Science, 2026)
This study examines the effects of dynamic capability and transformational leadership on organizational performance in public sector institutions by considering the institutional and bureaucratic characteristics that distinguish government organizations from private-sector entities. A quantitative survey approach was employed to investigate how adaptive organizational capabilities and leadership practices influence performance outcomes. A total of 150 questionnaires were distributed to structural and managerial officials in public organizations. Of these, 118 questionnaires were returned, 108 responses passed the initial screening process, and 100 valid cases were retained for the final analysis after data quality assessment. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that dynamic capability has a positive and significant effect on organizational performance (β = 0.31, p < 0.05), indicating that organizational adaptability enhances institutional effectiveness. Transformational leadership also demonstrates a positive and significant influence on performance (β = 0.51, p < 0.05), highlighting the importance of leadership behaviors in motivating employees and supporting organizational achievement. However, the interaction effect between dynamic capability and transformational leadership is not statistically significant. This study contributes to dynamic capability theory by identifying a public-sector-specific boundary condition: the performance benefits of dynamic capability are realized primarily through formalized procedures, administrative coordination, regulatory compliance, and accountability mechanisms rather than leadership-driven strategic flexibility. The findings extend dynamic capability theory to highly institutionalized public-sector environments and clarify how bureaucratic structures shape capability–performance relationships.